Heat stress stimulates colon cancer cells to secret specific population of extracellular nanovesicles enriched by HSP70 and microRNAs - I. V. Nazarova; L. M. Zabegina; N. S. Nikiforova; M. A. Slusarenko; E. I. Sidina; A. V. Zhakhov; A. M. Ishchenko; B. A. Margulis; I. V. Guzhova; A. V. Malek (Сибирский онкологический журнал)
Background. Heat stress (HS) induces the cellular secretion of heat shock proteins (HSP ) and extracellular nanovesicles (ENVs). The biological link between these phenomena is poorly understood. In the case of colorectal cancer (CRC) cells, the secretion of HSP s and ENV may be involved in the clinical response to intraperitoneal therapy of peritoneal carcinomatosis.Material and Methods. Established colon cancer cell lines COLO 320, HCT 116, HT29 and DLD 1 were used. ENVs were isolated from culture media by differential ultra-centrifugation and analyzed by dynamic light scattering, nanoparticle tracking analysis, atomic force microscopy and flow cytometry. Super-paramagnetic particles (SPMP ) covered by antibodies to the membrane form of Hsp70 were used for isolation and quantification of Hsp70(+) ENVs. Vesicular microRNA was assayed by RT-qPC R.Results. HS induces the secretion of ENVs by CRC cells, the resistance to HS correlates with the activity of HS-induced ENVs secretion. HS induces the secretion of a specific population of ENVs enriched by membrane form Hsp70 (mHsp70). The microRNA content of mHsp70(+) ENVs has qualitative and quantitative features. The concentration of miR-126-3p, -181-5p, -155-5p, -223 is increased in mHSP 70(+) ENVs secreted by three CRC cell lines.Conclusion. HS induces the secretion of mHSP 70(+) ENVs by CRC cells. This phenomenon may be involved in a clinical response to intraperitoneal chemo-hyperthermic perfusion therapy of peritoneal carcinomatosis.